2018
DOI: 10.1159/000486568
|View full text |Cite
|
Sign up to set email alerts
|

CSF-ctDNA SMSEQ Analysis to Tailor the Treatment of a Patient with Brain Metastases: A Case Report

Abstract: Brain metastases are the most common neurological complications of adult cancers, accounting for more than half of brain tumors. The incidence of brain metastases may be increasing due to improved detection of small lesions by advanced imaging technologies. Given the fast evolution of targeted and immunotherapy regimens, it is essential to serially assess brain malignancies during the disease course for disease monitoring and tailoring of the therapeutic management. For such serial and repetitive assessment, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Liquid biopsies collect and analyse circulating tumour cells (CTCs) and cell-free tumour (ctDNA) in body fluids (such as cerebrospinal fluid (CSF) and plasma); these can be a surrogate of tumour tissue in the management of both primary and secondary brain tumours [ 64 ]. For example, CSF ctDNA analysis has been successfully used in a case of multiple leptomeningeal and spinal cord metastases from CUP [ 65 ] (this case is discussed below).…”
Section: Gene Expression Profiling: a New Frontiermentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid biopsies collect and analyse circulating tumour cells (CTCs) and cell-free tumour (ctDNA) in body fluids (such as cerebrospinal fluid (CSF) and plasma); these can be a surrogate of tumour tissue in the management of both primary and secondary brain tumours [ 64 ]. For example, CSF ctDNA analysis has been successfully used in a case of multiple leptomeningeal and spinal cord metastases from CUP [ 65 ] (this case is discussed below).…”
Section: Gene Expression Profiling: a New Frontiermentioning
confidence: 99%
“…The problem of a lack of studies is even more evident in the subgroup of BM-CUP due to the rarity of cases, unfavourable prognosis, and frequent exclusion from clinical trials. Therefore, most information on innovative treatments comes from case reports [ 65 , 71 , 72 , 73 , 74 ]. Even if anecdotal, these reports offer good insight on feasible therapeutic strategies and potentially successful treatments in this rare and fatal disease ( Table 5 ).…”
Section: Managementmentioning
confidence: 99%
“…In addition to validation with peripheral blood, we have previously tested OncoLBx with other body fluids known to harbor ctDNA, such as pleural effusion and cerebral spinal fluid [4346]. In many of these cases, we are able to identify variants with therapy options from the non-blood body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is important to identify specific genomic mutations in the CSF and provide novel targeted therapeutic agents against these mutations in the treatment of BMs. Huang et al 68 identified somatic mutations in the CSF of a patient with metastatic brain adenocarcinoma of an unknown primary tumor using the SMSEQ NGS assay, and the patient was given tailored treatments that led to clinical remission. To put it briefly, a CSF-ctDNA analysis helps with the characterization of tumor mutational profiles that may refine the treatment protocols further and tailor the tumor management plan.…”
Section: Ctdna As a Predictive Biomarker Identifying Therapeutic Targetsmentioning
confidence: 99%